Disponibilidade mecânica de colhedoras de cana-de-açúcar: efeitos do tempo de uso na gestão da manutenção - Santanna, Alex Magno Gomes (Universidade Federal de São Carlos, 2020)
The mechanization of the Brazilian sugarcane harvest is important for the sugar and alcohol sector, since Brazil is the world's largest producer of this raw material. For this position to be maintained, an efficient management of the equipment involved in the cutting, transshipment and transportation of sugar cane is necessary, such as overflow tractors, harvesters and trucks. Harvesters play an important role in this process, as they are responsible for cutting, chopping and cleaning the sugar cane and all other equipment depends on its good performance. In this context, the present study aims to measure the availability of sugarcane harvesters throughout the harvest and for successive harvests and to analyze the performance of a sugarcane harvesting front with harvesters of different ages through a simulation model. The model developed was a cutting, transshipment and transportation front (CTT) composed of 4 harvesters, 8 transshipments and 6 trucks to carry out the sugarcane harvest and transport to the plant. The developed model was effective in representing the real system and provided information for analysis of availability. The scenarios used for simulation were composed by: (1) new harvesters; (2) 4 different and new harvesters: 1styear, 2nd year, 3rdyear and 4thyear of use; (3) 4 different and older harvesters: 3rdyear, 4thyear, 5thyear and 6thyear of use; (4) 4 harvesters with 6 years of use. The results obtained were consistent with the literature, with scenario 1 having the highest average availability, 95.9%, and the highest production of sugarcane. All scenarios showed a decline in their availability over the harvest season, as shown in the literature. It is also worth mentioning that the availability and time of use of the harvesters directly affected the production of the harvest front. The average result obtained from the group of six harvesters evaluated, regardless of the number of harvests worked, was an average reduction of 0.49% in availability per month. The loss of availability per crop year worked decreased by 1.75% per year, on average.
Mechanical availability of sugarcane harvesters: effects of time of use in maintenance management
Keywords: Simulação; Colheita; Disponibilidade; Simulation; Availability; Harvest; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL